Experience and satisfaction evaluation in fashion events - Liberato, Dália (2021)
Fashion events contribute to the enhancement of cities and regions as tourism destinations. The aim of this study is to understand the influence of the individual profile and characteristics of the trip in the evaluation of the experience considering the participation in fashion events and understand the influence of the experience of participation in the event, in the evaluation of the experience and the degree of satisfaction with the event. On the empirical side, using a quantitative methodology, the research presents a case study, investigating the relationship between the dimensions individual profile, characteristics of the trip, experience, current experience and satisfaction. Main findings show that Individual Profile, Characteristics of the Trip and Participation in Event positively affects the Evaluation of Experience, and Participation in the event positively affects the degree of satisfaction regarding the event. In terms of managerial implications, the authors suggest the existence of a mutual effect between the Individual Profile, the Characteristics of the Trip and the Knowledge and Participation in previous editions with the way that participants of fashion events will experience and evaluate their satisfaction regarding the event.